Accuracy of self-reported foot strike pattern detection among endurance runners - Vincent, H. K.; Coffey, K.; Villasuso, A.; Vincent, K. R.; Sharififar, S.; Pezzullo, L.; Nixon, R. M. (Frontiers in Sports and Active Living, 2024)
Introduction: Foot strike pattern is often associated with running related injury and the focus of training and rehabilitation for athletes. The ability to modify foot strike pattern depends on awareness of foot strike pattern before being able to attempt change the pattern. Accurate foot strike pattern detection may help prevent running related injury (RRI) and facilitate gait modifications and shoe transitions. The purposes of this study were to determine the accuracy of self-reported foot strike pattern among endurance runners, to identify what factors were predictive of accurate foot strike detection and recent RRI.